Reflexões sobre a gestão ambiental das Unidades de Conservação no estado do Amapá - Daguinete Maria Chaves Brito.; José Augusto Leitão Drummond. (Confins)
Amapá is the Brazilian state which has most of its territory set aside and managed as protected areas, particularly as federal and state parks, biological preserves, extractive preserves and productive forests. These areas are managed according to special rules and their main goal is to protect areas that have remarkable socioenvironmental features. This article deals with aspects of these areas related to their management practices. It aims to analyze the quality of these areas’ management. Methodological procedures combined updated data collection, based on the techniques of bibliographical, archival and legal research, with qualitative research. Our findings show that Amapá’ protected areas, created either by the federal or state government, display specific traits that limit their goal of preserving and conserving nature. Some of these traits are difficulties in drafting and applying management plans; conflicts with other land uses on account of land tenure insecurity; and environmental degradation caused by invaders who convert native vegetation into agricultural plots and pastures and practice predatory fishing.